Coherent control of four-wave mixing - Zhang, Yanpeng; SpringerLink (Online service). (Beijing Springer, 2011)
Coherent Control of Four-Wave Mixing discusses the frequency, temporal and spatial domain interplays of four-wave mixing (FWM) processes induced by atomic coherence in multi-level atomic systems. It covers topics in five major areas: the ultrafast FWM polarization beats due to interactions between multi-color laser beams and multi-level media; coexisting Raman-Rayleigh-Brillouin-enhanced polarization beats due to color-locking noisy field correlations; FWM processes with different kinds of dual-dressed schemes in ultra-thin, micrometer and long atomic cells; temporal and spatial interference between FWM and six-wave mixing (SWM) signals in multi-level electromagnetically induced transparency (EIT) media; spatial displacements and splitting of the probe and generated FWM beams, as well as the observations of gap soliton trains, vortex solitons, and stable multicomponent vector solitons in the FWM signals. The book is intended for scientists, researchers, advanced undergraduate and graduate students in Nonlinear Optics. Dr. Yanpeng Zhang is a professor and Zhiqiang Nie is a Ph. D. student at the Key Laboratory for Physical Electronics and Devices of the Ministry of Education, Xi'an Jiaotong University, China. Dr. Min Xiao is a professor of physics at the University of Arkansas, Fayetteville, U.S.A.
Introduction of Controllable Four-Wave Mixing (FWM) Processes -- Ultra-fast Polarization Beats Among FWM Processes -- Coexisting Brillouin, Rayleigh and Raman-enhanced FWM Processes -- Multi-dressing FWM Processes in Confined and Non-confined Atomic Systems -- Enhancement and Suppression in FWM Processes -- Modulating the FWM Processes via the Polarizable Dark States -- Controlling Spatial Shift and Splitting of FWM -- Spatial Solitons of FWM.
Electronic reproduction.
Keywords: Nonlinear optics; Electronic books